Linking Halal Requirement and Branding: An Examination of Halal Flight Kitchen Provider in Malaysia - Nor Aida Abdul Rahman; Mohamad Fakhrulnizam Mohamad; Jailani Muda; Md Fauzi Ahmad; Suzari Abdul Rahim; Zawiah Abdul Majid; Hazariah Md Noh (International Journal of Supply Chain Management, 2018)
There is something very appealing about Halal branding and its linked to Halal requirements. The establishment of Halal branding is actually closely related to Syariah compliance requirements. This study aims to explore how Halal branding is created in the context of Halal Flight Kitchen in Malaysia. This study adopted single case study method for deep exploration of the topic. This interpretive study opted for semi-structured interview, observation, and documents review as a main data collection method. Findings suggest proper segregation, sertu and workers hygiene are the three main elements to establish Halal branding in Halal flight kitchen. This study is among the pioneering research on Halal branding establishment from Flight Kitchen perspective